PIKETTY’S r>g THEORY RECONSIDERED FOR A TRANSITION ECONOMY - Fujita, Yasunori (International Journal of Research -GRANTHAALAYAH, 2025)
A substantial body of theoretical and empirical research has emerged to explore the relationship between the return on capital, economic growth, and inequality since Piketty and his coauthors offered a groundbreaking and comprehensive perspective on inequality. Bernardo, Martínez, and StockhammeA substantial body of theoretical and empirical research has emerged to explore the relationship between the return on capital, economic growth, and inequality since Piketty and his coauthors offered a groundbreaking and comprehensive perspective on inequality. Bernardo, Martínez, and Stockhammer (2014) lay out a post-Keynesian model to examine whether the condition ????????>???????? (where ???????? is the rate of return on capital and ???????? is the economic growth rate) necessarily brings about inequality. Jones (2015), by using an overlapping generations model, demonstrates that if ???????? and ???????? are constant values, degree of wealth inequality in the asset distribution depends on ????????−????????, and also that if ???????? adjusts to balance the supply and demand for capital, this difference converges to the population growth rate. Mankiw (2015) offers a recalibration of Piketty’s arguments by incorporating considerations such as consumption patterns, procreation, and taxation, to suggest that Piketty's pessimistic scenario is not consistent with historical evidence. Fujita (2015) contributes further by developing a theoretical model that distinguishes between real capital and financial capital to analyze how ????????>???????? affects the ratio of capital to income. This paper examines the issue from a different perspective. Specifically, it focuses on an economy consisting of laborers and capitalists transitioning from a barter-based system to a currency-based monetary system and demonstrates that inequality between laborers and capitalists does not increase in the short term, even when ????????>???????? holds.r (2014) lay out a post-Keynesian model to examine whether the condition r>g (where r is the rate of return on capital and g is the economic growth rate) necessarily brings about inequality. Jones (2015), by using an overlapping generations model, demonstrates that if r and g are constant values, degree of wealth inequality in the asset distribution depends on r-g, and also that if r adjusts to balance the supply and demand for capital, this difference converges to the population growth rate. Mankiw (2015) offers a recalibration of Piketty’s arguments by incorporating considerations such as consumption patterns, procreation, and taxation, to suggest that Piketty's pessimistic scenario is not consistent with historical evidence. Fujita (2015) contributes further by developing a theoretical model that distinguishes between real capital and financial capital to analyze how r>g affects the ratio of capital to income. This paper examines the issue from a different perspective. Specifically, it focuses on an economy consisting of laborers and capitalists transitioning from a barter-based system to a currency-based monetary system and demonstrates that inequality between laborers and capitalists does not increase in the short term, even when r>g holds.